Evolusi dan Struktur Pengetahuan Tanggung Jawab Sosial Perusahaan (CSR) Berbasis Olahraga: Analisis Bibliometrik menggunakan Basis Data Scopus - Septina, Trisha Aryanti; Apriantono, Tommy; Hasan, Muhamad Fahmi (Institut Teknologi Bandung, 2026)
Abstract Research on sport-based Corporate Social Responsibility (CSR) has developed rapidly and is no longer understood merely as a social activity but also as part of a sports organization’s sustainability strategy. This study aims to map the development, knowledge structure, and main themes in sport-based CSR research. The study employs a bibliometric analysis method using data from the Scopus database consisting of English-language journal articles from 2009 to 2025. The analysis was conducted using Microsoft Excel and VOSviewer to identify publication trends, productive authors, leading journals, and keyword network visualizations. The results indicate that publications on sport-based CSR have seen a significant increase, particularly after 2015, in line with growing attention to the Sustainable Development Goals (SDGs). The most dominant research themes relate to environmental sustainability, sports organization management, consumer behaviour, and organizational governance. Furthermore, the analysis indicates that sport-based CSR research is dominated by developed countries and focuses on sustainability issues within the sports industry. The study’s conclusions suggest that sport-based CSR research is evolving toward a more strategic and sustainability- oriented approach. This study is expected to serve as a reference for future sport- based CSR research. Keywords: bibliometric analysis, SDGs, sport-based CSR, sport management, VOSviewer.